ChemInform Abstract: A General Method for Imine Formation Using B(OCH2CF3)3. Issue 41 (October 2015) - Reeves, Jonathan T.; Visco, Michael D.; Marsini, Maurice A.; Grinberg, Nelu; Busacca, Carl A.; Mattson, Anita E.; Senanayake, Chris H.
Abstract The approach to various imines bearing different types of N‐substituents is possible under conditions A) or B).